2011
DOI: 10.1177/016173461103300403
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Attenuation and Backscatter Coefficient Estimates of Rodent-Tumor-Mimicking Structures: Comparison of Results among Clinical Scanners

Abstract: In vivo estimations of the frequency-dependent acoustic attenuation (α) and backscatter (η) coefficients using radio frequency (RF) echoes acquired with clinical ultrasound systems must be independent of the data acquisition setup and the estimation procedures. In a recent in vivo assessment of these parameters in rodent mammary tumors, overall agreement was observed among α and η estimates using data from four clinical imaging systems. In some cases, particularly in highly attenuating heterogeneous tumors, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 26 publications
(58 reference statements)
0
38
0
Order By: Relevance
“…This provides more evidence of the possibility of integrating spectral tissue characterization methods into clinical practice, even with new beamforming technologies. Historically, the implementation of spectral-based quantitative ultrasound techniques on clinical scanners has been deferred for a few reasons; in particular, the lack of access to RF signals and the absence of a consensus on the methodology of BSC estimation were early problems (Anderson et al 2010;Madsen et al 1999;Nam et al 2011). Today, most of these causes have been overcome.…”
Section: Discussionmentioning
confidence: 99%
“…This provides more evidence of the possibility of integrating spectral tissue characterization methods into clinical practice, even with new beamforming technologies. Historically, the implementation of spectral-based quantitative ultrasound techniques on clinical scanners has been deferred for a few reasons; in particular, the lack of access to RF signals and the absence of a consensus on the methodology of BSC estimation were early problems (Anderson et al 2010;Madsen et al 1999;Nam et al 2011). Today, most of these causes have been overcome.…”
Section: Discussionmentioning
confidence: 99%
“…The backscattered power spectrum received from a region of interest (ROI) is analyzed to fit the tissue typing parameters to these models. [7][8][9][10][11][12][13][14][15] In the case of prostate cancer, ultrasound has been used for cancer detection both based on texture analysis in B-mode images [16][17][18][19] and based on spectral analysis of raw ultrasound RF signals. 20 The most successful methods combine the tissue typing features from B-mode and RF data.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial pulse length or simply the pulse length can then be calculated by multiplying time pulse length with the speed of sound and dividing by 2. Our prior studies have shown that expressing resolution in pulse length and number of independent echoes is a relatively independent method for comparing the results from different ultrasound systems and scans [61,62].…”
Section: Methodsmentioning
confidence: 99%